Unravelling structural and mechanistic elements of catalytic subunits A and coupling subunit F and structural and kinetic studies of the A3B3D and A3B3DF-subcomplexes of the Methanosarcina mazei Gö1 provide insights into the single molecule dynamics of this engine - Singh, Dhirendra (2017)
ATP synthases and ATPases are membrane-bound enzymes that synthesize either ATP from ADP and phosphate by utilizing the electro-chemical potential of the membrane or generate electro-chemical potential by hydrolysing ATP, respectively. The ATP synthases found in archaeal cell membranes are mainly known as A-ATP synthases. The unique ability of archaea to grow on low energy substrates and thrive on harsh environmental conditions separates them from other domains of life and therefore A-ATP synthases are believed to be strongly related to the predecessor of the ATP synthases/ases. Unravelling their structural and functional aspects will provide a deep insight into the evolutionary pathway of ATP synthases/ases. A-ATP synthases (A1AO ATP synthases) are multi-subunit complexes with the subunit composition and stoichiometry of A3:B3:D:F:(EG)2:C:a:cX, whose functioning is determined by the coordination of these subunits. Several studies have been carried out on A-ATP synthases addressing the question of ion-coupling in the membrane-embedded AO-domain and ATP synthesis in the A3B3D-hexamer via the central stalk subunits C, D and F. However, details of the mechanistic coupling elements of subunit F, the nucleotide binding A-B interface, and the proposed rotating central stalk subunits (D and F) of this molecular engine are missing. In the present study, the role of subunit F as a stimulator of ATPase activity in the A3B3DF-complex of Methanosarcina mazei Gö1 (Mm) ATP-synthase is established with the combinatorial studies using electron microscopy and enzyme kinetics. Further, C-terminal deletions and mutations of subunit F revealed its importance in enhancing the ATPase activity. In another study, crystals of the A3B3D-complex of M. mazei Gö1 ATP-synthase were obtained and optimized for the purpose of retrieving information about the interface of subunits A and B of this enzyme complex. The mechanistic studies were carried out on the MmA3B3DF complex, and its angular velocities were determined using gold-nanorod and compared to the distantly related eubacterial F-ATP synthases. ATP synthases are described to have mechanisms which regulate the unnecessary depletion of ATP pool during an energy limited state of the cell. Mg-ADP inhibition is one of the regulatory features where Mg-ADP gets entrapped in the catalytic site, preventing the binding of ATP and further inhibiting ATP hydrolysis. V-ATPases are ATP-driven proton pumps and localized in eukaryotic vacuoles, Golgi-derived vesicles, lysosomes, synaptic vesicles etc. They are mainly involved in membrane trafficking, cellular pH homeostasis, and neurotransmitter secretion. Currently, Mg-ADP inhibition is not observed in V-ATPases and to understand the involvement of their P-loop (phosphate binding loop) in shielding them from Mg-ADP inhibition, the P-loop of V-ATPases (257GAFGCGKTV265) was mimicked in A-ATP synthases (234GPFGSGKTV242). The P-loop of V-ATPases and A-ATP synthases are mostly identical with differences in only two residues. These two residues of A-ATP synthases (proline and serine) were mutated to alanine and cysteine, respectively, in MmA3B3D and MmA3B3DF. The enzymatic assays revealed a decrease of ATP binding affinities for the mutated complexes (MmA3B3D and MmA3B3DF). In addition, the dismissal of Mg-ADP inhibition was observed in the mutated MmA3B3DF complex. The mutations were incorporated in the individual catalytic subunit A of A-ATP synthase and alterations in substrate-binding were studied by fluorescence correlation spectroscopy and X-ray crystallography.